1999
DOI: 10.1093/oxfordjournals.aje.a009930
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Exposure to Environmental Tobacco Smoke and High Density Lipoprotein Cholesterol among Nonsmokers

Abstract: There are few epidemiologic studies among adult nonsmokers on the effects of workplace environmental tobacco smoke on high density lipoprotein cholesterol (HDL-C). The authors investigated this relation, using data from health examinations conducted in 1995 on 3,062 Japanese nonsmokers in a total of 27 municipal offices with few smoking restrictions. Multiple regression analysis with adjustments for age, body mass index, alcohol drinking, and sports activities showed that in women, and in men lacking both alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…74 Passive smoking leads to lower levels of HDL in adults. 75,76 Passive smokers (exposed to SHS for Ն6 h/d for Ն4 d/wk for at least the past 6 months) had HDL levels of 48.26Ϯ3.47 (meanϮSD) mg/dL compared with 55.59Ϯ4.24 mg/dL in those unexposed to SHS. HDL levels in passive smokers were indistinguishable from levels in active smokers (45.59Ϯ4.6 mg/dL) ( Table 2).…”
Section: Effects On Hdlmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Passive smoking leads to lower levels of HDL in adults. 75,76 Passive smokers (exposed to SHS for Ն6 h/d for Ն4 d/wk for at least the past 6 months) had HDL levels of 48.26Ϯ3.47 (meanϮSD) mg/dL compared with 55.59Ϯ4.24 mg/dL in those unexposed to SHS. HDL levels in passive smokers were indistinguishable from levels in active smokers (45.59Ϯ4.6 mg/dL) ( Table 2).…”
Section: Effects On Hdlmentioning
confidence: 99%
“…Nonsmoking women in the middle tertile and highest tertiles of SHS exposure were 1.7 (95% CI 1.2 to 2.5) and 1.6 (95% CI 1.1 to 2.4) times more likely to have low levels (Ͻ45 mg/dL) of HDL than those in with the lowest intensity of exposure, respectively. 76 Acute exposure to SHS also lowers HDL levels. Moffat et al 78 exposed 12 male subjects to 6 hours of SHS at concentrations similar to those found in a bar.…”
Section: Effects On Hdlmentioning
confidence: 99%
“…16,17 In adults, heavy workplace exposure to tobacco smoke has been demonstrated to have an adverse influence on serum lipids. 18,19 Recently, it was indicated that maternal smoking in pregnancy is associ- 21 Exposure to tobacco smoke as indicated by objective measurement, serum cotinine concentration, has been frequently determined in school-aged children. The aim of the present study was to examine the effects of frequent exposure to tobacco smoke on vascular wall structure, endothelial function, and serum lipid profile in healthy 13-year-old adolescents.…”
mentioning
confidence: 99%
“…16,17 In adults, heavy workplace exposure to tobacco smoke has been demonstrated to have an adverse influence on serum lipids. 18,19 Recently, it was indicated that maternal smoking in pregnancy is associ-ated with an increase in total cholesterol levels and trends toward adverse lipoprotein profiles in the young adult offspring. 20 However, there are no data on the relations of exposure to tobacco smoke and apolipoprotein (Apo) levels in children or adolescents.…”
mentioning
confidence: 99%
“…Specifically, SHS exposure can lower high-density lipoprotein (HDL) cholesterol levels as well as the levels of antiatherogenic lipoprotein subfractions (eg, HDL 2 ) [43][44][45]. These effects have been described in adults and children and are comparable in magnitude to those observed in active smokers.…”
Section: Other Effectsmentioning
confidence: 97%